Fazendo arranjos para piano solo de obras de Luizinho Duarte: entrevistas, estratégias e exemplos - Costa, Tarcísio Paulo da (2023)
The main focus of this work is the creation of an arrangement for solo piano. Having as general objective to identify procedures used in the creation of these. For this purpose, the following specific objectives were defined: conceptualize arrangements, understand the creative process of pianists, prepare three arrangements of pieces by composer Luizinho Duarte and describe the procedures used to create the arrangements. Approaching this theme is justified because the understanding and description of these procedures can guide others who want to dedicate themselves to this activity, increasing the collection of pieces arranged for solo piano, directly or indirectly impacting the interested community. The present study consists of an action-research, with a qualitative treatment of the data, which includes a bibliographic study on the theme and interviews with six Brazilian pianists with great visibility in the current scenario: André Mehmari, Hercules Gomes, Gilson Peranzzetta, Salomão Soares , Thiago Almeida and Uaná Barreto. As a result, three arrangements were created, and their creative process was documented and described. It is hoped that this work can inspire others who deal with this theme, as well as instigate a deep reflection about the creativity involved in the artistic process.